Simultaneous Production of Biosurfactants and Bacteriocins by Probiotic Lactobacillus casei MRTL3 - Deepansh Sharma; Baljeet Singh Saharan (International Journal of Microbiology)
Lactic acid bacteria (LAB) are ubiquitous and well-known commensal bacteria in the human and animal microflora. LAB are extensively studied and used in a variety of industrial and food fermentations. They are widely used for humans and animals as adjuvants, probiotic formulation, and dietary supplements and in other food fermentation applications. In the present investigation, LAB were isolated from raw milk samples collected from local dairy farms of Haryana, India. Further, the isolates were screened for simultaneous production of biosurfactants and bacteriocins. Biosurfactant produced was found to be a mixture of lipid and sugar similar to glycolipids. The bacteriocin obtained was found to be heat stable (5 min at 100°C). Further, DNA of the strain was extracted and amplified by the 16S rRNA sequencing using universal primers. The isolate Lactobacillus casei MRTL3 was found to be a potent biosurfactant and bacteriocin producer. It seems to have huge potential for food industry as a biopreservative and/or food ingredient.